General Lexicology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Lexicology, the examination of words and their meanings, is fundamental to linguistics since it explores the structure, evolution, and function of vocabulary in languages. Despite considerable progress, a large gap remains in comprehending the dynamic interplay between lexical systems and modern linguistic transformations influenced by digital communication, globalisation, and cultural hybridity. This study investigates general lexicology, focussing on the identification of new lexical patterns and the incorporation of neologisms into established linguistic structures. The study utilises a mixed-methods approach, integrating corpus analysis of modern literature and surveys of linguistic usage among various demographic groups. The study examines language corpora from internet platforms, academic publications, and ordinary communication to identify patterns in semantic shifts, word development, and loanword assimilation. Research indicates a significant rise in semantic fluidity, with words adopting new meanings more rapidly than in earlier periods, largely driven by technological progress and worldwide connectivity. Moreover, neologisms are frequently contingent upon context, mirroring socioeconomic and cultural subtleties. The findings emphasise the flexibility of lexicons in adapting to external linguistic influences and stress the necessity of contemporary lexicographic methods to document these changes. The consequences of this study include to language instruction, AI-facilitated natural language processing, and intercultural communication, providing resources for traversing a changing linguistic environment. The research enhances comprehension of words as a dynamic, adaptable system integral to human interaction.